Antidiabetics activity of salam koja (murraya koenigii ) leaves tea bag - Widayanti, Ari; Srifiana, Yudi; Efendi, Kriana (Pharmaceutical Sciences and Research, 2019)
Koja bay leaves (Murraya koenigii) which mostly cultivated in Indonesia and the leaves usually used by Aceh people as a flavoring agent for food, has been known to have an antidiabetic effect.. In this study, we analyzed the antidiabetic effect of koja bay leaves tea bags which commercially available. Methods: The two variant doses of koja bay leaves tea bag (411.11 mg/g body weight and 822.22 mg/g body weight) were administered to 25 male rats which divided into five groups. The antidiabetic activity was determined by measuring blood glucose of rats administered by koja bay leaves tea bag compared to blood glucose of rats in positive control which was given glibenclamide negative control, and normal control. Results: The results showed that dose 1 and 2 decreased blood glucose level by 51.27% and 45.17%, respectively, fairly similar to the glibenclamide (63.38%). Conclusion: Koja bay leaves tea bag have comparable activity with glibenclamide in reducing the blood glucose level.